Differential spectrometrics of acid solutions - Ng Jia Jia (2019)
Extensive Research have been conducted as protonated aqueous solutions, H-X (X=I, Cl, Br) are universally vital in areas ranging from biochemistry to pharmaceutical sciences. However, the interactions between H+ protons and X- anions remains unsolved.